From Fiction to Ethical Encounter: Problematization as Method in J.M. Coetzee’s Narratives - ELGARHI, Nabit (International Journal of Language and Literary Studies, 2025)
This article examines J.M. Coetzee’s literary practice as a philosophical methodology rooted in the Foucauldian notion of "problematization." This paper contends that Coetzee’s work should not be confined to the realm of traditional philosophical fiction; instead, it operates as an ethically charged interrogation of alterity, freedom, and justice, thereby transforming literature into a platform for critical epistemological engagement. By engaging with the ideas of Michel Foucault, Emmanuel Levinas, and Jacques Derrida, this study situates Coetzee at a critical juncture where literary aesthetics converge with ethical critique. Problematization works not solely as a rhetorical strategy but as a critical tool for unveiling the contingencies and power dynamics inherent in historical and narrative constructions. This article posits that Coetzee’s fiction is intricately connected to ethical performance and epistemic responsibility, asserting that his body of literature embodies a form of writing-as-resistance that deliberately eschews resolution in favour of continuous ethical exploration. The argument reaches its apex with the assertion that Coetzee’s fiction exemplifies an ethics-first philosophy, emphasising the significance of engaging with the Other and the unsettling openness inherent in narrative. In this endeavour, Coetzee fundamentally reinterprets the function of literature within the frameworks of postmodernism and postcolonialism.